Desolation island - O'Brian, Patrick, 1914-2000 (O'Brian, Patrick, 1914-2000. Aubrey/Maturin novels, 2021)
"Commissioned to rescue Governor Bligh of Bounty fame, Captain Jack Aubrey and his friend and surgeon Stephen Maturin sail the Leopard to Australia with a hold full of convicts. Among them is a beautiful and dangerous spy-and a treacherous disease that decimates the crew. With a Dutch man-of-war to windward, the undermanned, outgunned Leopard sails for her life into the freezing waters of the Antarctic, where, in mountain seas, the Dutchman closes"--